Discovery of young, oxygen-rich supernova remnants in PHANGS-MUSE galaxies - Kravtsov, T.; Anderson, J. P.; Kuncarayakti, H.; Maeda, K.; Mattila, S. (EDP SCIENCES S A, 2026)
Context. Supernova remnants (SNRs) are the late stages of supernovae (SNe) before they merge to the surrounding medium. Oxygen-rich (O-rich) SNRs represent a rare subtype with strong visible-light oxygen emission.
Aims. We present a new method to detect SNRs exploiting the capabilities of modern visible-light integral-field units based on the shapes of the SNR emission lines.
Methods. We search for unresolved shocked regions with broadened emission lines using the medium-resolution integral-field spectrograph MUSE on the Very Large Telescope. The spectral resolving power allows shocked emission sources to be differentiated from photoionised sources based on the linewidths. Results. We find 307 SNRs, including seven O-rich SNRs. For all O-rich SNRs, we observe the  [O III]λλ4959,5007  emission doublet. In addition, we observe emissions from [O I] λλ6300,6364, [O II] λλ7320,7330, H alpha+[N II]λ6583 and [S II]λλ6717,6731 to varying degrees. The linewidths for the O-rich SNRs are generally broader than the rest of the SNRs in the sample of this article. The oxygen emission complexes are reminiscient of SNR 4449-1 and some long-lasting SNe. For the O-rich SNRs, we also search for counterparts in archival data of other telescopes; we detect X-ray and mid-IR counterparts for a number of remnants.
Concluions. We have shown the efficacy of the method in detecting SNRs presented in this article. In addition, the method is also effective in detecting the rare O-rich SNRs, doubling the sample size in the literature. The origin of O-rich SNRs and their link to specific SN types or environments is still unclear, but further work into this new sample will unquestionably help us shed light on these rare remnants.